Green advertising is more environmentally friendly? The influence of advertising color on consumers’ preferences for green products - Wenting, Feng; Yuelong, Zeng; Xianyun, Shen; Chenling, Liu (Frontiers in Psychology, 2022)
The color of green product advertisements is an important factor affecting consumers’ preferences. Based on the theory of the self-control system, this paper explores the influence mechanism and boundary conditions of green product ad color on consumers’ preferences through three experiments. Experiment 1 tested the effect of advertisement color type (green/color) on consumers’ preferences for green products. The results show that color ad can promote consumers’ preferences for green products compared with green ad. Experiment 1 also analyzed the mediating role of the self-control system between advertisement color type (green/color) and consumers’ preferences. Experiment 2 further clarified the boundary of the main effect. The effect of ad color (green/color) on consumers’ preferences was only effective in the context of green products. Experiment 3 explored the moderating effect of green product type (egoistic/altruistic) on the main effect. The results show that only when the green product type is altruistic, the ad color type (green/color) can significantly affect consumers’ preferences. This study is the first to link the ad color of green products with consumers’ preferences. The findings confirm that the use of color ad for green products can elicit higher consumers’ preferences than pure green ad, which enriches the research on the color of green product advertisements.